Effects of hypertonic and hypotonic saline infusion on renal functions in induced hyperthyroid and hypothyroid dogs - Suwanna Songsataya (Chulalongkorn University, 1984)
The effects of hypertonic and hypotonic saline intrarenal infusion on renal functions were studied in experimental hypothyroid and hyperthyroid dogs. Seventeen adult male mongrel dogs were devided into three groups : group I as control, group II as hypothyroidism (by surgical thyroidectomy) and group III as hyperthyroidism (by daily subcutaneous injection of L-thyroxine 0.1 mg/kg for 1 week). Either hypertonic (537 mOsm/kg) or hypotonic (27 mOsm/kg) saline was directly infused into the left or right renal artery at the rate of 2.0 ml/min instead of the isotonic saline solution (290 mOsm/kg) as in the control group. The contralateral kidney was used to compare with the other one throughout the experimental peroid. The present study showed that cardiac output (co), blood volume (BV), mean arterial pressure (MAP) and total peripheral resistance (TPR) did not change significantly in hypothyroid group but heart rate (HR) decreased significantly compared with the same state of the control group. Glomerular filtration rate (GFR) and viii renal blood flow (RBF) decreased by approximately 10% and 21% respectively but renal vascular resistance (RVR) increased by approximately 5%. The urinary excretion of sodium ( UNaV ) decreased by approximately 11% whereas the urinary excretion of potassium (UKV), chloride (UCiV), calcium ( UCaV) and inorganic phosphorus (UPiV) changed slightly. In the hyperthyroid animal, there was a significant increase in HR while no significant alterations of BV, MAP and TPR were observed. Co increased by approximately 54% as compared with the control state of the control animal. GFR and RBF increased by approximately 16% and 52% respectively but RVR decreased by approximately 19%. UNAV, UCIV, UcaV and UpiV increased by approximately 111%, 205%, 114% and 93% respectively whereas UV increased significantly. Infusion of hypertonic saline solution, raising sodium concen tration in that renal artery to 2.67 + 1.81 (Mean ± S.D.) uEq/ml/min, caused a significant increase in V, UNaV, UK V and UPiV of the infused kidney in the control animals. GFR and RBF increased by approximately 13% and 9% whereas RVR decreased by approximately 5%. U CaV and U.PiV increased slightly. The rise in renal fraction despite a non-significant change in RBF, GFR and MAP during hypertonic saline infusion in the control animals showed that there was a vasodilatation of the infused kidney. The renal hemodynamics of the contralateral kidney did not change markedly as compared with the control state of the same kidney.Effect of hypertonic saline solution on the infused kidney in the hypothyroid animals caused an increase in v, UNAV, UCIV, UcaV and UpiV and RVR by approximately 63%, 40% 15%, 59%, 11% and 24% respectively but UCaV decreased slightly as compared with the control state of the same kidney. GFR decreased significantly in the both kidneys. UKV increased markedly in the contralateral kidney while RBF, UK, UCIV, UcaV and UpiV changed slightly. A reduction in GFR and RBF of the infused kidney since co, MAP and TPR did not changed significantly showed a local vasoconstriction during hypertonic saline infusion in the hypothyroid animals. Hypertonic saline infusion was administered into the hyper thyroid animals caused a slight increase in UNAV, UCIV, UcaV and UpiV of the infused kidney. GFR, RBF and U V decreased insignificantly as compared with the control state of the same kidney. RVR increased markedly in the both kidneys indicated that there was a local vasoconstrictions of the kidneys during hypertonic saline infusion in the hyperthyroid animals. Effects of hypertonic saline infusion induced diuresis of the infused kidney judging from an increase in V and UNaV in three groups. Infusion of hypotonic saline solution lowering renal arterial plasma sodium concentration to 2.87 ± 1.94 (Mean ± S.D.) uEq/ml/min, caused a significant increase in RVR whereas a significant decrease in RBF of both kidneys in the control animals. GFR decreased slightly in the both kidneys. During hypotonic saline infusion in the hyper thyroid animals, GFR decreased markedly in the both kidneys that related to an increase in RVR. RBF decreased insignificantly in the both kidneys. The urinary excretions of electrolytes and the rate of urine flow were not significantly decreased in the both kidneys of the control and hyperthyroid animals except the slight increase in U V of the contralateral kidney in the control animals. These results showed that there was a local vasoconstriction of the both kidneys in the control and hyperthyroid animals during hypotonic saline infusion. In the hypothyroid animals, hypotonic saline infusion caused a significant decrease in V and UKV whereas a slight decrease in GFR, RBF, UCIV, UcaV and UpiV of the infused kidney. RVR was increased slightly. The contralateral kidney did not changmarkedly. Effect of hypotonic saline infusion has been shown that there was a local vasoconstriction of the infused kidney judging from an increase in RVR in all groups of the animals. These results suggest that kidneys can function as primary effector to the hypertonic and hypotonic saline solutions introduced directly into them. The mechanisms of physiological changes in the hyperthyroid and hypothyroid animals are not clear, the possibility may be the intrarenal hormonal changes and/or the intrarenal regulators.